The Influence of Entrepreneurship Education and Entrepreneurial Attitude on Juvenile Prisoner’s Entrepreneurial Intention in 3 Provinces of Indonesia - Hamenda, Bobby; Hamenda, Andress (International Journal Of Management And Economics Invention, 2021)
This study discovers the influence of entrepreneurship education on juvenile prisoners’ entrepreneurial intentions in LPKA Batam, Pangkalpinang and Medan located in 3 provinces in Indonesia while also evaluating their entrepreneurial attitude as a mediating variable. An examination was held based on the 30 surveys collected to assess for the relationships. It is exhibited that entrepreneurship education in the 3 juvenile prisons significantly impacts on juvenile prisoners’ entrepreneurial intentions through the crucial roles of entrepreneurial attitude. The findings revealed that entrepreneurship education influences entrepreneurial intentions indirectly through entrepreneurial attitude in which its role is a complete mediation to entrepreneurial intentions. The results also recommended that government of Indonesia with their influential policy can embrace entrepreneurship education to form juvenile prisoners’ entrepreneurial attitude to improve young prisoners’ entrepreneurial intentions. Additionally, the strategic value of these findings is also as the resource to encourage government, academicians, enterprises with their corporate social responsibility, and community at large to play their roles in improving entrepreneurship education for juvenile prisoners in Indonesia.